PERKEMBANGAN KAJIAN MEMBACA PEMAHAMAN PADA JENJANG PENDIDIKAN DASAR TAHUN 2014-2024 - Suarjaya, Ignatius Dimas Adi; Widharyanto, B.; Nugraha, Setya Tri; Kunjana Rahardi, R. (Jurnal Dedikasi Pendidikan, 2025)
Reading comprehension is a crucial indicator of students' literacy, yet in Indonesia, this skill remains underdeveloped, as evidenced by consistently low PISA rankings. This study aims to describe the progress of research on students' reading comprehension in Indonesia over the past decade and assess how these studies contribute to understanding the issue of low literacy skills. The study employs a library research method, analyzing 18 scholarly articles indexed in SINTA 3 and 4 between 2014 and 2024. The findings reveal that from 2014 to 2019, research focused on developing learning models and strategies, such as SQ3R and multiliteracy, which proved effective in enhancing reading comprehension. Between 2020 and 2022, the focus shifted to analyzing reading comprehension levels, while 2023–2024 explored innovative methods leveraging technology. Although these strategies show positive impacts, challenges persist, particularly in consistent implementation and teachers' limited creativity in applying new techniques. This study highlights the need for ongoing collaboration among educators, policymakers, and researchers to improve reading comprehension in Indonesia through technology-based approaches and more intensive teacher training programs